2015
DOI: 10.1614/wt-d-15-00006.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carrier Volume on Grain Sorghum Response to Simulated Drift of Nicosulfuron

Abstract: Research was conducted in 2010 and 2012 to determine the effect of simulated drift of nicosulfuron on growth and yield of grain sorghum. Herbicide rates represented 25, 12.5, and 6.3% of the use rate of nicosulfuron at 52 g ai ha−1. Nicosulfuron was applied in a constant carrier volume of 224 L ha−1where herbicide concentration decreased with reduction in rate, and in carrier volumes of 56, 28, and 14 L ha−1proportional to the 25, 12.5, and 6.3% herbicide rates, respectively. In 2010, grain sorghum injury and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Nicosulfuron, which is labeled in Inzen™ grain sorghum, caused 49% injury to conventional sorghum (Table 3). These results were consistent with previous studies of injury to conventional grain sorghum applied with nicosulfuron, which showed levels ranging from 19% to 67% depending upon rate applied (Matocha and Jones 2015).…”
Section: Sensitivity To Pre Applications Of Als-inhibiting Herbicidessupporting
confidence: 93%
“…Nicosulfuron, which is labeled in Inzen™ grain sorghum, caused 49% injury to conventional sorghum (Table 3). These results were consistent with previous studies of injury to conventional grain sorghum applied with nicosulfuron, which showed levels ranging from 19% to 67% depending upon rate applied (Matocha and Jones 2015).…”
Section: Sensitivity To Pre Applications Of Als-inhibiting Herbicidessupporting
confidence: 93%
“…Matsum. & Nakai] (Al-Khatib et al 2003; Bailey and Kapusta 1993; Culpepper et al 2018; Ellis et al 2002, 2003; Ellis and Griffin 2002; Matocha and Jones 2015; Steppig et al 2017). Collectively, they evaluated 2,4-D, dicamba, glufosinate, glyphosate, halosulfuron, imazethapyr, mesotrione, nicosulfuron, primisulfuron, quizalfop, propanil, sethoxydim, and tembotrione.…”
Section: Introductionmentioning
confidence: 99%
“…Matsum. & Nakai] (Al- Khatib et al, 2003;Bailey and Kapusta, 1993;Culpepper et al, 2018;Ellis et al, 2002Ellis et al, , 2003Ellis and Griffin, 2002;Matocha and Jones, 2015;Steppig et al, 2017). Collectively, they evaluated 2,4-D, dicamba, glufosinate, glyphosate, halosulfuron, imazethapyr, mesotrione, nicosulfuron, primisulfuron, quizalfop, propanil, sethoxydim, and tembotrione.…”
mentioning
confidence: 99%